Projetos de educação e civilidade : controle social e disciplinarização dos costumes em Uberabinha, MG (1888-1926) - Ching, Handel Carrera (2010)
This search sought to understand the construction of representations concerning to the ideal citizen for the new society of the Brazilian First Republic (1889-1930). The problem we aimed to answer through this research regards to the representations of the idealized citizen built by local newspapers in the city of Uberabinha on the period from 1888 to 1926. To better understand the qualifications of the new citizen and the republican society we plotted as specific goals the understanding of work positivity explicit in local newspapers and in criminal proceedings; the analysis of social groups that had their way of life and how they reorganized themselves during the attempted reordering and cleaning of public urban space; to conclude, we aimed to understand the role of primary school to the achievement of ideal citizen for this desired new society. To answer these questions, we used as documentary source local newspapers, criminal proceedings, Proceedings of the City Council, Municipal Code of postures and Laws and Statutes of Uberabinha. Our results have revealed that in a period in which the educational institution had not established itself inward the state of Gerais, the "space producers" used the journals as a strategy to highlight their citizenship plans of patriotism and civility. The defendants from the poor classes defend themselves using speech that was close to the dominant groups, an example of appropriation and (re) signification of the strategies made by the weak to get rid of the stigma of felon or subversive. The formation of the first elementary school in Uberabinha still was, over this period, insufficient to achieve the national representations of the republican ideal citizen and therefore the elites propagated their ideas through press.